Robust monetary policy, structural breaks, and nonlinearities in the reaction function of the Central Bank of Brazil - Gabriela Bezerra de Medeiros; Marcelo Savino Portugal; Edilean Kleber da Silva Bejarano Aragón (EconomiA, 2016)
In this work, we seek to investigate the existence of nonlinearities in the reaction function of the Central Bank of Brazil arising from this policymaker's uncertainties about the effects of the output gap on inflation. Theoretically, we follow Tillmann (2011) to obtain a nonlinear optimal monetary policy rule that is robust to uncertainty about the output-inflation trade-off of the Phillips Curve. In addition, we perform structural break tests to assess possible changes in the conduct of the Brazilian monetary policy during the inflation-targeting regime. The results indicate that: (i) the uncertainties about the slope in the Phillips curve implied nonlinearities in the Central Bank of Brazil's reaction function; (ii) we cannot reject the hypothesis of a structural break in the monetary rule parameters occurring in the third quarter of 2003; (iii) there was an increase in the response of the Selic rate to output gap and a weaker response to the current inflation gap in Meirelles–Tombini's administration; and (iv) the Central Bank of Brazil has also reacted to the exchange rate in Meirelles–Tombini's administration.